2005
DOI: 10.1080/00288306.2005.9515103
|View full text |Cite
|
Sign up to set email alerts
|

Modelling loess landscapes for the South Island, New Zealand, based on expert knowledge

Abstract: In New Zealand, occurrence of loess often determines the spatial pattern of soil depth, and influences droughtiness, leaching potential, organic matter accumulation, nutrient retention, and natural plant-species distribution. Understanding loess distribution is therefore a major prerequisite for soil and land resource management. Although New Zealand's soil scientists have accumulated a good empirical knowledge of loess distribution through several decades of field investigation, only some of this knowledge is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Loess textural variation is consistent with downwind fining from the source area (Young, 1964;Ruhe, 1969;Mason et al, 1999), with resultant influences on soil morphology: well-drained fine sandy Laminar Pallic Soils (Haplustalfs) are found adjacent to the Waitaki River while Perch-Gley Pallic Soils (Inceptisols) further south are comprised mainly of silts with fragic and reductimorphic features. Soil maps and conceptual soil-landscape models have been used to infer loess distribution (Mason et al, 1999;Schmidt et al, 2005a), and the 1:50,000-scale soil map of the study area and associated soillandscape models of Wilson (1970) may be used in this way. Wilson (1970) divided North Otago into distinct physiographic regions defined according to their lithology and pattern of landform components (e.g.…”
Section: The Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Loess textural variation is consistent with downwind fining from the source area (Young, 1964;Ruhe, 1969;Mason et al, 1999), with resultant influences on soil morphology: well-drained fine sandy Laminar Pallic Soils (Haplustalfs) are found adjacent to the Waitaki River while Perch-Gley Pallic Soils (Inceptisols) further south are comprised mainly of silts with fragic and reductimorphic features. Soil maps and conceptual soil-landscape models have been used to infer loess distribution (Mason et al, 1999;Schmidt et al, 2005a), and the 1:50,000-scale soil map of the study area and associated soillandscape models of Wilson (1970) may be used in this way. Wilson (1970) divided North Otago into distinct physiographic regions defined according to their lithology and pattern of landform components (e.g.…”
Section: The Study Areamentioning
confidence: 99%
“…Loess maps derived from these models were more accurate and had greater resolution than earlier maps, and they provided a more detailed description, including uncertainties, of extent, depth, and pattern of loess distribution within loess-landscapes. Schmidt et al (2005a) concluded, however, that these models needed to be refined and tested by higher-resolution studies in selected areas, with quantitative models complemented by intensive field data.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations